Medication and ECG Patterns That May Hinder SPECT Myocardial Perfusion Scans - Marko Magdi Abdou Sidrak; Maria Silvia De Feo; Joana Gorica; Ferdinando Corica; Miriam Conte; Luca Filippi; Giuseppe De Vincentis; Viviana Frantellizzi (MDPI AG, 2023)
Coronary artery disease (CAD) is the leading cause of death followed by cancer, in men and women. With risk factors being endemic and the increasing costs of healthcare for management and treatment, myocardial perfusion imaging (MPI) finds a central role in risk stratification and prognosis for CAD patients, but it comes with its limitations in that the referring clinician and managing team must be aware of and use at their advantage. This narrative review examines the utility of myocardial perfusion scans in the diagnosis and management of patients with ECG alterations such as atrioventricular block (AVB), and medications including calcium channel blockers (CCB), beta blockers (BB), and nitroglycerin which may impact the interpretation of the exam. The review analyzes the current evidence and provides insights into the limitations, delving into the reasons behind some of the contraindications to MPI.